A longitudinal study of the association between depression, anxiety and stress symptoms of university students in Serbia with excessive social media use before and during COVID-19 pandemic - Višnjić, Aleksandar; Kök, Kıvanç; Višnjić, Jovana; Jovanović, Tamara; Marković, Roberta (Frontiers in Public Health, 2023)
Background: Besides the well known good side of social media, it cannot be denied some of its negative effects. This two-phase study aimed to find out whether the usage of social media during the COVID-19 pandemic showed some significant association with depression and anxiety symptoms, and levels of stress.The study was based on the survey of 1,476 randomly selected students at the initial phase (December 2019 to February 2020), and 1,400 students of the same cohort at the follow up phase (December 2021 -February 2022). The collected data included sociodemographics, social media usage aspects, and the ones concerning levels of depression, stress and anxiety symptoms. Standardized questionnaires -the Bergen Social Media Addiction Scale (BSMAS) was applied to measure the levels of social media addiction, and the Depression Anxiety Stress Scale (DASS 42) was administered to evaluate the symptoms of depression, anxiety and stress.The comparison of responses regarding the six components of online social media addiction, which constitute the BSMAS, between the two phases of the study showed significant difference (p<0.01) in favor of the follow up phase in the raised scores of all but one component. The probable severe or extremely severe symptoms of depression, anxiety, and stress were notably enhanced during the peak of pandemic, and all three of them were positively correlated with all 6 BSMAS components (p<0.01). The results also indicate that students who consumed alcohol beverages and psychoactive substances more frequently in the pandemic, exhibited more noticeable symptoms of depression (p<0.01, for both associations). Higher levels of anxiety symptoms in students were found to be associated with longer sleep during the night (p<0.01), increased alcoholic beverages consumption (p<0.01). Stress levels had the strongest correlations with consuming alcoholic beverages during the pandemic (r=0.16, p<0.01).The comparison between two phases of this follow-up study revealed significant changes in the Internet usage characteristics, which may have had an essential influence on the investigated symptoms of depression, anxiety, and stress. However, other factors that may have influenced student's mental health during the COVID-19 pandemic should also be considered.